A Study of the Relationship between Research Output and National Productivity Development in the Mekong Region - Katemukda, Nichanach (Journal of Mekong Societies, 2024)
Enhancement of productivity is crucial for national development in the Mekong region (China, Thailand, Cambodia, Laos, Myanmar, and Vietnam). This study aims to investigate potential positive relationships between research output and national productivity. Research output consists of the number of documents, citable documents, citations, self-citations, and citations per document. A correlation analysis was conducted using meta data from the World Bank and SCImago covering the period from 1996 to 2021. The findings reveal that the number of published documents has the strongest positive correlation with national productivity in all countries. The number of documents and citable documents are positively related in 99 percent of the six countries, reflecting a shared effort to generate citable documents. Self-citations show a stronger positive relationship with national productivity than external citations, although both are less influential than the number of documents and citable documents. Linear regression analysis further indicates that the number of published documents is the primary driver of national productivity, with an adjusted R-squared value of 55% at a 95% confidence interval. The study suggests that governments in the Mekong region should encourage researchers to publish a sufficient quantity and quality of research papers. Additionally, they should support research institutes and universities in developing their own Scopus-indexed journals to facilitate knowledge exchange. By increasing knowledge in the region, long-term national productivity can be significantly enhanced.